Fatty acids promote M1 polarization of monocyte-derived macrophages in healthy or ketotic dairy cows and a bovine macrophage cell line by impairing mTOR-mediated autophagy - Sun, Xudong; Gao, Shuang; Chang, Renxu; Jia, Hongdou; Xu, Qiushi; Mauck, John; Loor, Juan J.; Li, Xiaobing; Xu, Chuang (Journal of dairy science, 2024)
The list of standard abbreviations for JDS is available at adsa.org/jds-abbreviations-24. Nonstandard abbreviations are available in the Notes. Excessive concentrations of free fatty acids (FFA) are the main factors causing immune dysfunction and inflammation in dairy cows with ketosis. Polarization of macrophages (the process of macrophages freely switching from one phenotype to another) into M1 or M2 phenotypes is an important event during inflammation induced by environmental stimuli. In nonruminants, mammalian target of rapamycin (mTOR)-mediated autophagy (a major waste degradation process) regulates macrophage polarization. Thus, our objective was to unravel the role of mTOR-mediated autophagy on macrophage polarization in ketotic dairy cows. We performed 4 experiments: (1) In vitro differentiated monocyte-derived macrophages from healthy dairy cows or dairy cows with clinical ketosis (CK) were treated for 24 h with 100 ng/mL LPS and 100 ng/mL IFN-γ or with 10 ng/mL IL4 and 10 ng/mL IL10; (2) Immortalized bovine macrophages were treated for 24 h with 0, 0.3, 0.6, or 1.2 mM FFA, LPS, and IFN-γ, or with IL4 and IL10; (3) Macrophages were pretreated with 2 μM 4,6-dimorpholino-N-(4-nitrophenyl)-1,3,5-triazin-2-amine (MHY1485) for 30 min before treatment with LPS and IFN-γ or IL4 and IL10; (4) Macrophages were pretreated with 100 nM rapamycin (RAPA) for 2 h before treatment with LPS and IFN-γ or IL4 and IL10. Compared with healthy cows, cows with CK had a greater mean fluorescence intensity (MFI) of CD86+, but lower MFI of CD206+ and lower number of autophagosomes and autolysosomes in macrophages. Exogenous FFA treatment upregulated protein abundance of inducible nitric oxide synthase (iNOS) and the MFI of CD86, whereas it downregulated the protein abundance of arginase 1 and the MFI of CD206. In addition, FFA increased the p-p65/p65 protein abundance and tumor necrosis factor α, IL1B, and IL6 mRNA abundance, but decreased LC3-phosphatidylethanolamine conjugate protein abundance and the number of autophagosomes and autolysosomes number. Pretreatment with MHY1485 promoted macrophage M1 polarization and inhibited macrophage M2 polarization via decreased mTOR-mediated autophagy. Activation of mTOR-mediated autophagy by pretreatment with RAPA attenuated the upregulation of inflammation in M1 macrophages that was induced by FFA. These data revealed that high concentrations of FFA promote macrophage M1 polarization in ketotic dairy cows by impairing mTOR-mediated autophagy.